ANXIETY, DEPRESSION, DYSFUNCTION OF THE AUTONOMIC NERVOUS SYSTEM AND THEIR CORRELATIONS DURING COVID-19 PANDEMIC - Zaporozhets, T.M.; Korovina, L.D.; Sukhomlyn, T.A.; Mishchenko, I.V.; Sukhomlyn, A.A. (World of Medicine and Biology, 2023)
The purpose of the study was to explore correlations between psychological and regulatory mechanisms in the development of autonomic nervous system dysfunction in response to stressors during the COVID-19 pandemic. 133 students were examined. HADS, PSS-10, State-aR questionnaires were used. Dysfunction of the autonomic nervous system was determined according to A.M. Wein and based on heart rate variability analysis. 37.0 % of respondents had symptoms of anxiety, 38.1 % had subclinical and clinical symptoms of depression, 99.1 % had a moderate and high level of subjective stress. Altered heart rate variability was noted in individuals with subclinical and clinical signs of depression. There were positive correlations between levels of anxiety and depression (R=0.50, p
Keywords: stress; anxiety; depression; autonomic nervous system; COVID-19 pandemic; international students